Fabrication and photophysical studies of CdTe quantum-dots dispersed in SiO2 sonogel optical-glasses - Morales Saavedra, Omar G.; Gutiérrez Lazos, Claudio Davet; Ortega López, Mauricio; Rodriguez Rosales, Antonio A. (2015)
The catalyst-free sonogel route has been implemented to fabricate highly pure SiO2 glasses as host materials for CdTe quantum dot nanocrystals synthesized in aqueous solution. Developed CdTe-based inorganic–inorganic hybrid composites exhibited rigid bulk structures with controllable geometrical shapes and dopant concentrations, allowing the control of the optical properties in the solid-state confinement. Comprehensive linear and nonlinear photophysical characterizations were performed according to UV–vis absorbance, Raman and photoluminescent spectroscopies; the linear refractive indices of highly/lowly CdTe-doped samples were also estimated according to the Brewster angle technique. Since the hybrid glasses are amorphous in nature, the cubic nonlinear optical activity of these composites has been tested via the Z-Scan technique. Results show that the CdTe quantum dots were homogeneously embedded within the SiO2-sonogel matrix with only small guest–host molecular interactions and preserving their strong photoluminescent properties; thus providing advanced solid-state heterostructured nanocomposite materials suitable for current technological photonic applications.